A Comparison Analysis of Spatial Structure of Traditional Chinese and Korean Residences Based on Spatial Syntax. Issue 6 (March 2019) - Zhang, Yaolong; Chen, Yang; Wang, Jingjing
Abstract: The traditional dwellings of China and South Korea reflect the basic living space of the two peoples at that time. They reproduce the social reality through the organization of space. It is a cultural product that reflects social reality.This study selects the representative examples of traditional residential buildings in China and South Korea.Based on the space syntax theory, analysis software such as depthmap and axwomen are used to analyze the similarities and differences between the spatial specific variable values, including integration, connectivity and control value.And through the above analysis, combined with the correlation between space and cultural connotation:(1)The quadrangle dwellings in China has a relatively shallow spatial structure compared to the Jeong-On's Traditional House in Korean, but the identifiable spatial structure in the two cases is similar.(2)The quadrangle dwellings is different from the courtyard in the Jeong-On's Traditional House in the entire space structure, and its connection center is the corridor space.The corridor plays the role of transition space in the interior space of the courtyard, and divides the spatial hierarchy according to the depth.(3)South Korea is a space of dual power structure, which is influenced by class and gender in the formation of spatial structure, while China has a very vertical order, but in a highly controlled space, The influence of class and gender can be ignored.This study will help us to further strengthen our understanding of the traditional living space of the two countries. we can point the way for us to explore non-standardized and new types of living in the future.